FAKTOR RESIKO YANG BERHUBUNGAN DENGAN RIWAYAT SERANGAN PADA PENDERITA ASMA DI KABUPATEN MINAHASA SELATAN - Manese, Mercy; Bidjuni, Hendro; Rompas, Sefti (JURNAL KEPERAWATAN, 2021)
Abstract: The background of this journal is that the asthma risk factors that influence thedevelopment and expression of asthma consist of internal factors (host factors) and externalfactors (environmental factors). The purpose of this study was to determine the risk factorsassociated with a history of attacks in asthmatic patients at motoring health centers, westmotoring health centers and east motoring health centers. The research method usesdescriptive research with a cross sectional approach with total sampling technique, in thisstudy totaling 30 respondents, with research instruments consisting of allergens, respiratoryfactors, environmental factors and weather changes, with univariate and biavariate dataanalysis. The results showed that there was a relationship between allergen factors and ahistory of asthma attacks with p value = 0.033 < = 0.05, there was a relationship betweenrespiratory infection factors and a history of asthma attacks with p = 0.011 < = 0.05, therewas no relationship between factors environment with a history of asthma attacks with p value= 0.749 < = 0.05, there is a relationship between weather change factors and a history ofasthma attacks with p = 0.027 < = 0.05. In conclusion, there is a relationship between allergenfactors, infection factors and change factors with history of asthma attacks. Suggestions forthe community to definitely know the triggering factors for bronchial asthma attacks so thatthey can prevent asthma recurrence and can avoid sudden changes in weather, for examplefrom hot to cold (rainy season) by using thick clothing.Keywords: Asthma risk trigger factors, history of asthma attacksAbstrak: Latar Belakang dari jurnal ini adalah Faktor risiko asma yang mempengaruhiperkembangan dan ekspresi asma terdiri dari faktor internal (host factor) dan faktor eksternal(environmental factor). Tujuan penelitian ini adalah untuk mengetahyui faktor resiko yangberhubungan dengan riwayat serangan pada penderita asma puskesmas motoling, puskesmasmotoling barat dan puskesmas motoling timur. Metode penelitian menggunakan penelitiandeskriptif dengan pendekatan cross sectional dengan teknik total sampling, pada penelitian iniberjumlah 30 responden, dengan instrumen penelitian yang teridiri dari faktor alergen, faktorsaluran pernafasan, faktor lingkungan dan perubahan cuaca, dengan analisa data univariat danbiavariat. Hasil penelitian didapatkan bahwa ada hubungan faktor alergen dengan riwayatserangan asma dengan nilai p = 0,033 < Î± =0,05, ada hubungan faktor saluran infeksipernapasan dengan riwayat serangan asma dengan nilai p = 0,011 < Î± =0,05, tidak adahubungan faktor lingkungan dengan riwayat serangan asma dengan nilai p = 0,749 < Î± =0,05,ada hubungan faktor perubahan cuaca dengan riwayat serangan asma dengan nilai p = 0,027 <Î± =0,05.Kesimpulan, terdapat hubungan faktor alergen, faktor infeksi dan faktor perubahandengan riwayat serangan asma. Saranmsyarakat secara pasti mengetahui faktor pencetusserangan asma bronkial agar dapat mencegah kekambuhan asma dan dapat menghindariperubahan cuaca yang mendadak misalnya dari panas ke dingin (musim hujan) denganmenggunakan pakaian tebal.Kata Kunci : Faktor pemicu risiko asma, riwayat serangan asma